Comparison of various diagnostic and therapeutic modalities of undescended testis - Swami, Ganesh Ashok; Bansod, Himanshu (International Surgery Journal, 2021)
Background: Undescended testes (UDT), which are defined as the failure of testes to descend in scrotum. It is the most common developmental defect in male infants. It is recorded in 30% of preterm infants compared with 3% of term infants. Methods: Convenient sampling method for data collection, clinical palpation, ultrasound, magnetic resonance imaging (MRI), endoscopic ultrasound, laparoscopic methods for detection and therapeutic management. Results: Laparoscopy has proven to be the only diagnostic modality where the findings provide a clear dependable direction for the definitive management of impalpable testes, so it allows an accurate diagnosis and definitive treatment in the same sitting. Conclusions: Diagnostic imaging has no role in the routine evaluation of boys with undescended testes. Laparoscopy in impalpable testes is the procedure of choice and allows definitive management, even when conversion to open procedure is necessary.